What do consumer and providers view as important for integrated care? A qualitative study - Ann Carrigan; Natalie Roberts; Robyn Clay-Williams; Peter Hibbert; Elizabeth Austin; Diana Fajardo Pulido; Isabelle Meulenbroeks; Hoa Mi Nguyen; Mitchell Sarkies; Sarah Hatem; Katherine Maka; Graeme Loy; et al. (BMC, 2023)
Abstract Background Integrated care is a model recognised internationally, however, there is limited evidence about its usability in the community. This study aimed to elicit community and provider views about integrated care and how implementation could meet their healthcare needs in a new hospital. Methods Using a qualitative approach, consumer and provider views on the strengths, barriers and enablers for integrated care were collected via a series of online workshops and supplementary interviews. Results A total of 22 consumers and 49 providers participated in 11 focus groups; all perceived integrated care to be an accessible and efficient model that offers a high level of care which enhanced staff and patient well-being. Providers expressed concerns about longer waiting times and safety risks associated with communication gaps and insufficient staff. Enablers include supporting consumers in navigating the integrated care process, co-ordinating and integrating primary care into the model as well as centralising patient electronic medical records. Discussion Primary, tertiary and community linkages are key for integrated care. Successful interoperability of services and networks requires an investment in resources and infrastructure to build the capability for providers to seamlessly access information at all points along the patient pathway. Conclusion Integrated care is perceived by consumers and providers to be a flexible and patient-focused model of healthcare that offers benefits for a hospital of the future.